A new species of Smicridea McLachlan 1871 (Trichoptera: Hydropsychidae) from the Caatinga biome and new distributional records from Brazil - Alves, André Almeida; Santos, Allan Paulo Moreira; Nessimian, Jorge Luiz (Zootaxa, 2018)
A new species of Smicridea (Smicridea) McLachlan 1871 is described and illustrated based on specimens collected from the Caatinga biome, in Sete Cidades National Park, Piauí state, and Ubajara National Park, Ceará state, northeastern Brazil. Based on phallus morphology, Smicridea (Smicridea) caatinga sp. nov. belongs to the S. nigripennis Group and can be distinguished from other species in this group due to the phallus having two ventral sclerotized projections and, when expanded, two dorsal membranous lobes and one ventrolateral membranous lobe with two spines on the apex. New distributional records of Smicridea species are provided for different Brazilian states: S. (S.) aequalis Banks 1920 for Ceará and Piauí, S. (Rhyacophylax) coronata Flint 1980 for Rio Grande do Sul and Piauí; S. (R.) jundiai Almeida & Flint 2002 for Mato Grosso; S. (R.) marlieri Flint 1978 for Roraima; S. (R.) palmar Sganga 2005 for Goiás; S. (S.) paranensis Flint 1983 for Ceará and Piauí; and S. (R.) spinulosa Flint 1972 for Rio Grande do Sul. Furthermore, S. (S.) erecta Flint 1974b is recorded for the first time for Brazil, in Amazonas state. [Zoobank: urn:lsid:zoobank.org:act:3C2892F9-D430-492B-98DA-A48569253A63]